2007
DOI: 10.4049/jimmunol.178.10.6051
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-Specific T Cells of Nonobese Diabetic Mice Recognize a Weak MHC-Binding Segment in More Than One Form

Abstract: Several naturally occurring anti-insulin CD4 T cells were isolated from islet infiltrates of NOD mice. In accordance with the results of others, these T cells recognized the segment of the β-chain from residues 9–23. Peptides encompassing the B:(9–23) sequence bound weakly to I-Ag7 in two main contiguous registers in which two residues at the carboxyl end, P20Gly and P21Glu, influenced binding and T cell reactivity. Naturally occurring insulin-reactive T cells exhibited differing reactivities with the carboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
108
2
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 46 publications
(65 reference statements)
6
108
2
1
Order By: Relevance
“…The IC 50 values for the B:(9-23) peptide were measured in the 5-10 μM range at endosomal pH and the half-life of the complexes was less than two hours. Recently, a detailed analysis of the binding of this epitope to I-A g7 was made which confirmed these general findings and revealed several interesting new features [41]. First, the B:(9-23) peptide bound weakly to I-A g7 in two contiguous registers, using two neighboring binding core segments, as shown in Table 3.…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thsupporting
confidence: 56%
See 2 more Smart Citations
“…The IC 50 values for the B:(9-23) peptide were measured in the 5-10 μM range at endosomal pH and the half-life of the complexes was less than two hours. Recently, a detailed analysis of the binding of this epitope to I-A g7 was made which confirmed these general findings and revealed several interesting new features [41]. First, the B:(9-23) peptide bound weakly to I-A g7 in two contiguous registers, using two neighboring binding core segments, as shown in Table 3.…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thsupporting
confidence: 56%
“…Binding of Insulin B Chain Peptides b b Binding analysis of synthetic peptides to soluble I-A g7 . Binding studies were performed at pH 5.5 [41]. Replacement of the natural residues with lysines allowed for the identification of the P9-MHC contact amino acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,22,38,39 Recent studies in NOD mice showed that the InsB12-20 and InsB13-21 peptides are the core nonamers for IA g7 binding and induced T-cell reactivity in the NOD mouse. 40,41 Within InsB12-23 four binding registers exist capable of binding this molecule. Although in appearance IA g7 and HLA-DQ8 appear similar, yet there are subtle differences that may affect peptide binding and T-cell recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Each binding register creates a unique set of upward pointing amino acid side-chains for T-cell recognition and also exhibits a distinct binding affinity for MHC class II conferred by the downward-facing amino acids that occupy its binding pockets. The Unanue group first reported that B:9-23 can be presented by IA g7 in either R1 or R2 and that each register is recognized by a different set of B:9-23-spepcifc CD4 + T cells (8). In contrast, a separate study (9,10) reported that T cells recognize the B:9-23 peptide bound to IA g7 in R3, the weakest binding of the three registers.…”
mentioning
confidence: 99%